Analysis Of User Satisfaction Towards The ShopeePay Application Using The EUCS (End User Computing Satisfaction) Method - Rafeda Ramma, Rafif; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
This study examines user satisfaction with the ShopeePay application using the End User Computing Satisfaction (EUCS) method. Despite some negative feedback regarding the payment system’s limitations and complexity, the research employed a quantitative approach with 160 respondents selected through purposive sampling. Data analysis was conducted using SmartPLS with Partial Least Squares Structural Equation Modeling (PLS-SEM) techniques to assess user satisfaction. The findings reveal that overall, users are satisfied with the ShopeePay application, indicating a positive reception of the platform. This research contributes to understanding consumer attitudes towards digital payment applications and provides insights for improving user experience in the rapidly evolving fintech sector. The study’s methodology and results offer valuable information for both researchers and practitioners in the field of mobile payment systems and user satisfaction analysis.